Partial left ventriculectomy: a retrospective study Ventriculectomia parcial esquerda: uma análise retrospectiva - Marcelo Campos Christo (Brazilian Journal of Cardiovascular Surgery, 2003)
OBJECTIVE: To identify useful predictive data on chance mechanisms of postoperative outcome, the impact on symptoms of terminal heart failure - after partial left ventriculectomies (PLV) - was critically evaluated through the analysis of results, on accumulated descriptive data on reports, between 1995 and 1998. METHOD: Available routine clinical data on surgical aspects and clinical outcomes were gathered and, when possible, validated for comparative analysis. RESULTS: PLV can provide a significant short to medium term amelioration in the quality-of-life in event-free survivors, but it was also watched out that in important proportion of them - as an evolutive sequence - PLV was incapable of changing the myocardial fibers leading tendency to conservatism of the preoperative vicious geometric dynamic pattern in late evolution. Importantly, the LV end-diastolic echocardiographic diameter of 7.5 cm (± 1.4 cm) was the steadiest quantitative significant numerical appeal to heart reduction surgery, in a setting of 465 patients, aged two to 74 years. And in a succession of individual reports of PLV results, whose mortality varied from 0 a 60%, survival after PLV showed a significant relationship with morphologic evolution of cardiomyocytes, in postoperative, and augmented in absolute values in patients with progressive ventricular dysfunction, treated with the insertion of LVAD (Left Ventricular Assist Devices). CONCLUSION: The material impossibility of identifying useful qualified predictors on chance mechanisms of postoperative outcome emerged as the crucial limitation for current usage of surgical reversal of left ventricular structural chamber dilation - to treat dilated cardiomyopathies - despite accumulated numerical values and clinical experiences. OBJETIVO: Este estudo foi empreendido para identificar fatores que poderiam ter contribuído para o decréscimo da mortalidade e da morbidade em pacientes submetidos a ventriculectomia parcial esquerda (VPE) pela análise de dados descritores de resultados acumulados, a partir de diferentes publicações seqüenciais, entre 1995 e 1998. MÉTODO: Dados clínicos rotineiros, envolvendo aspectos cirúrgicos e resultados pós-operatórios, foram reunidos e, quando possível, selecionados para análise comparativa. RESULTADOS: A VPE foi capaz de possibilitar uma melhora muito significativa no desempenho da função sistólica e da qualidade de vida dos sobreviventes livres de eventos, mas também pode ser claramente verificado que, numa importante proporção destes sobreviventes - como uma seqüência evolutiva - a VPE foi incapaz de modificar a tendência das fibras miocárdicas de retornar ao modelo do pré-operatório, na evolução tardia. Além disso, o diâmetro diastólico final - ecocardiograficamente avaliado - de 7,5 cm (±1,4 cm) foi o suporte quantitativo mais significativo para a indicação da VPE, em uma coorte de 465 pacientes de dois a 74 anos de idade. Em uma sucessão de resultados individuais nos quais a mortalidade pós-operatória oscilou de 0 a 60%, a sobrevivência à VPE mostrou relação significativa com a evolução da morfologia da célula miocárdica no pós-operatório e aumentou exponencialmente, em termos absolutos, quando pacientes com aumento persistente da disfunção ventricular foram tratados com dispositivo de assistência ao ventrículo esquerdo. Left Ventricular Assist Device (LVAD). CONCLUSÃO: A impossibilidade material de identificar preditores qualificados das chances de evolução pós-operatórias emergiu como uma limitação crucial para o uso rotineiro da reversão cirúrgica da dilatação da cavidade ventricular para tratar cardiomiopatias dilatadas, a despeito da experiência e dos valores numéricos acumulados.